2017
DOI: 10.1007/s10549-017-4371-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative paravertebral blocks for the management of acute pain following mastectomy: a cost-effectiveness analysis

Abstract: Over a broad range of probabilities, PPVB in mastectomy reduces postoperative pain at an acceptable incremental cost compared to GA. Commercial payers should be persuaded to reimburse this technique based on convincing evidence of cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…paracetamol, NSAIDs or COX‐2 selective inhibitors) in a fully implemented multimodal analgesia programme. Not surprisingly, a cost effectiveness study reported higher costs of continuous paravertebral block ; however, these costs would be offset by the reduced duration of hospital stay . Interfascial plane blocks also improve postoperative analgesia with lower pain scores and opioid consumption than general anaesthesia alone.…”
Section: Discussionmentioning
confidence: 99%
“…paracetamol, NSAIDs or COX‐2 selective inhibitors) in a fully implemented multimodal analgesia programme. Not surprisingly, a cost effectiveness study reported higher costs of continuous paravertebral block ; however, these costs would be offset by the reduced duration of hospital stay . Interfascial plane blocks also improve postoperative analgesia with lower pain scores and opioid consumption than general anaesthesia alone.…”
Section: Discussionmentioning
confidence: 99%
“…There are some local or regional nerve blocks in breast cancer performed as core components of multimodal analgesia and enhanced recovery after surgery (ERAS) ( 12 ), including thoracic epidural ( 13 ), interscalene brachial plexus ( 14 ), paravertebral ( 15 ), pectoral nerve blocks ( 16 , 17 ), and erector spinae plane block ( 18 ). Ultrasound-guided serratus anterior plane block (SAPB) is a new analgesic technique applied to the clinic proposed by Blanco ( 19 ); it is a block in which local anesthetic is deposited within an interfascial plane either superficial or deep into the serratus anterior muscle at the mid-axillary line ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using a cost‐utility approach is that there are a range of acceptable values for the incremental cost per QALY gained, termed the incremental cost‐effectiveness ratio, which enables fair comparisons for treatments regardless of the disease or problem it is intended to treat (Shiroiwa et al., ). An alternative approach, which has been used to calculate the cost‐effectiveness of interventions intended to improve outcomes relevant to patient comfort previously, is the willingness to pay method (Offodile et al., ; Pritchard et al., ). Using this method, FAW could be considered cost‐effective for procedures performed with sedation in a cardiac catheterisation laboratory if the extra cost of an incremental gain in thermal comfort is less than the decision maker's willingness to pay for it.…”
Section: Introductionmentioning
confidence: 99%